Revised subfamily classification for Polygonaceae, with a tribal classification for Eriogonoideae (2011)
Recent phylogenetic studies have provided a revised hypothesis of the evolutionary relationships within Polygonaceae, particularly regarding placement of certain tropical taxa. Based on phylogenetic data, we recognize three subfamilies: Eriogonoideae, Polygonoideae, and Symmerioideae. Within the Eriogonoideae we accept six tribes, two of which, Leptogoneae and Gymnopodieae, are new.